Oil Tanker Trucks And Their Impact On The Fluidity Of Road Transport On The International Highway: A Case Study From International Highway In Iraq - Abd Allateef Jbara, Suzan (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
The growing dependence on oil tanker trucks for transporting petroleum products along Iraq’s International Highway has raised major concerns regarding traffic fluidity, road safety, and infrastructure resilience. This study investigates the specific impact of these heavy vehicles on traffic congestion, speed reduction, and road surface deterioration. The research aimed to: (1) analyze how oil tanker trucks affect traffic flow in terms of congestion, delays, and speed variation; (2) evaluate the capacity and condition of road infrastructure under heavy vehicle pressure; and (3) recommend effective traffic and infrastructure management strategies. A mixed-methods approach was employed, combining GPS tracking, ITS-based traffic monitoring, radar speed detection, and manual vehicle counts, along with surveys and interviews conducted with truck drivers, road users, and transport authorities. The results show that oil tanker trucks reduce the average vehicle speed from 75 km/h to 40–50 km/h, increase travel delays by up to 25%, and significantly accelerate pavement damage, particularly near toll booths and refueling stations. Stakeholder feedback revealed a consensus on the need for immediate interventions. The study recommends implementing dedicated truck lanes, time-based truck movement restrictions, and investment in intelligent transportation systems (ITS) to enhance traffic efficiency and minimize infrastructure wear. These findings offer vital insights for improving transport policy, road safety, and long-term highway sustainability in Iraq.